Maldives Economic Update, September 2011 - World Bank (Washington, DC, 2017)
Tourism sector growth continues to be robust in 2011, consolidating the strong rebound in real Gross Domestic Product, or GDP growth in 2010. Real GDP growth is estimated to be 8.3 percent in 2011, down from 9.9 percent in 2010. Fast growing tourism receipts are supporting higher than expected government revenue outcomes. Recently introduced tax reforms, particularly the tourism goods and services tax, will put medium term fiscal sustainability on a firmer footing. Nevertheless, fiscal consolidation remains the policy priority for the authorities. Discussions with the International Monetary Fund or IMF on a program of support will resume this quarter. to see if agreement can be reached on measures that ensures medium-term fiscal and debt sustainability Domestic financing of the unsustainable fiscal deficit and rising international commodities prices continue to put pressure on the demand for foreign currency. Consequently, foreign reserves have resumed their downward trend after the boost from one-off privatization receipts. Uncertainty related to the recent devaluation of the Rufiyaa has subsided, but it is still trading at the upper end of the band and there remains an approximately 10 percent parallel market premium. The inflationary effects of the devaluation are now being felt with consumer price inflation rising to double digits in recent months.